Deregulation of Lipid Homeostasis: A Fa(c)t in the Development of Metabolic Diseases - Cisa-Wieczorek, Sabina; Hernández-Alvarez, María Isabel (Cells (Basel, Switzerland), 2020)
Lipids are important molecules for human health. The quantity and quality of fats consumed in the diet have important effects on the modulation of both the natural biosynthesis and degradation of lipids. There is an important number of lipid-failed associated metabolic diseases and an increasing number of studies suggesting that certain types of lipids might be beneficial to the treatment of many metabolic diseases. The aim of the present work is to expose an overview of de novo biosynthesis, storage, and degradation of lipids in mammalian cells, as well as, to review the published data describing the beneficial effects of these processes and the potential of some dietary lipids to improve metabolic diseases.